2019
DOI: 10.21873/anticanres.13222
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-induced Rat Mammary Carcinomas Are Mainly of Luminal Subtype and Have Multiple Copy Number Aberrations

Abstract: to understand the subtype(s) of these carcinomas for which the incidence was increased following neutron exposure. We also clarified the DNA copy number aberrations of these mammary carcinomas to elucidate the mechanisms of neutron-induced carcinogenesis. Materials and Methods Tissue samples. Tumor samples were obtained from our previous study (8), which was approved by the Institutional Animal Care and Use Committee of National Institute of Radiological Sciences. Briefly, in that previous study, 7-week-old fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(34 reference statements)
2
3
1
Order By: Relevance
“…Third, it is unclear whether the mammary carcinoma subtype is strain-dependent. Our previous studies on mammary carcinomas of (SD×COP)F 1 (n = 24 tumors) and SD (n = 85 tumors) rats indicated that they are mainly (70%-90%) of the luminal subtype [22,32,33], consistent with reports from other laboratories [47,48]. Further studies are required to clarify if this applies to COP rats, as the number of tumors obtained in our study was small (n = 9) due to the high resistance of the strain.…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…Third, it is unclear whether the mammary carcinoma subtype is strain-dependent. Our previous studies on mammary carcinomas of (SD×COP)F 1 (n = 24 tumors) and SD (n = 85 tumors) rats indicated that they are mainly (70%-90%) of the luminal subtype [22,32,33], consistent with reports from other laboratories [47,48]. Further studies are required to clarify if this applies to COP rats, as the number of tumors obtained in our study was small (n = 9) due to the high resistance of the strain.…”
Section: Plos Onesupporting
confidence: 90%
“…Previous studies have shown that radiation-induced mammary carcinomas of SD rats harbor multiple copy-number aberrations that do not converge to specific chromosomal regions [26,32,33]. In surprising contrast, our present analysis of mammary carcinomas (n = 21) from (SD×COP)F 1 rats revealed multiple copy-number variations in several specific chromosomal regions (Fig 2A).…”
Section: Mammary Carcinomas Of (Sd×cop) F 1 Rats Have Multiple Localized Copynumber Variationscontrasting
confidence: 70%
See 1 more Smart Citation
“…The peripubertal peak of the age-at-exposure dependence suggests its association with the very rapid cell proliferation that occurs during puberty [ 26 ]. The genome of radiation-induced rat mammary cancer frequently displays large structural abnormalities [ 27–29 ], suggesting the influence of error-prone end-joining machinery. The effect of Brca1 knockout on radiation-induced mammary carcinogenesis was minimal in rats irradiated immediately after, but not before, puberty [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stochastic effects, generally late effects such as carcinogenesis, are probabilistic in nature. Although the impact of neutrons on stochastic effects is not clear, the stochastic effects of neutrons and mixed-field exposures are being studied, as demonstrated by the available literature on carcinogenic effects of neutrons (37)(38)(39)(40). However, further research is needed to improve understanding of the risk associated with exposures below the level at which deterministic effects occur.…”
Section: Neutron Radiobiologymentioning
confidence: 99%